2022
DOI: 10.4028/p-354i45
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of the Use of Ground Glass Break in the Production of Aerated Concrete

Abstract: The possibility of using breakage of technical glass in conjunction with liquid glass to obtain aerated concrete by low-power technology is considered. The necessary strength is provided by finely ground unsorted breakage of technical glass with a specific surface area of 450, 500 and 550 m2/kg. The compressive strength of aerated concrete samples is 0.08; 0.25 and 1.8 MPa, and the bending strength is 0.04; 0.08 and 0.33 MPa, accordingly. The optimum is grinding to a specific surface area of 500-550 m2/kg, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Consequently, further grinding is impractical, since with an increase in the duration of grinding, the energy consumption of this process increases significantly. In preliminary experiments [42,43], it was found that the formation of cellular concrete with acceptable strength characteristics under air cured conditions is achieved at the following ratios of raw components: liquid glass 28-32 wt.% (ρ = 1230-1350 kg/m 3 ), polydisperse cullet 38-47 wt.%, Portland cement 9-12 wt.%, sodium hexafluorosilicate 3.5-4.5 wt.%, sodium hydroxide 2.5-3.5 wt.%, aluminum powder 1-1.2 wt.%, water 8-9 wt.%. When preparing the cement paste, liquid glass and water were added to the thoroughly mixed solid components.…”
Section: Composition Morphology and Dispersion Of Technical Glass Wastementioning
confidence: 99%
“…Consequently, further grinding is impractical, since with an increase in the duration of grinding, the energy consumption of this process increases significantly. In preliminary experiments [42,43], it was found that the formation of cellular concrete with acceptable strength characteristics under air cured conditions is achieved at the following ratios of raw components: liquid glass 28-32 wt.% (ρ = 1230-1350 kg/m 3 ), polydisperse cullet 38-47 wt.%, Portland cement 9-12 wt.%, sodium hexafluorosilicate 3.5-4.5 wt.%, sodium hydroxide 2.5-3.5 wt.%, aluminum powder 1-1.2 wt.%, water 8-9 wt.%. When preparing the cement paste, liquid glass and water were added to the thoroughly mixed solid components.…”
Section: Composition Morphology and Dispersion Of Technical Glass Wastementioning
confidence: 99%